SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN BARU PADA PT KINGSLEE INFINITAS TEKNOLOGI - Triandy, Oky; Tukino, Tukino (Computer Science and Industrial Engineering, 2021)
The acceptance of new prospective employees at a company is very important for the company because employees are the company's main asset which aims to increase productivity and performance. Basically, the purpose of selecting new employee candidates is to get the right candidate for a certain position so that the new employee candidate can work optimally and can survive for a longer period of time therefore there should be no mistakes in recruitment. At PT Kingslee Infinitas Teknologi, which is engaged in a distributor that requires a large number of employees for Stock Management, Sales Management, Supply Chain Management, Financial Management and Accounting. then this company is looking for prospective employees who have the skills and abilities required for the job. In some companies the process of hiring new employees is still not done professionally. This can occur because some companies rarely apply systematic standard methods in assessing prospective new employees. Decision support system for hiring new employees built with the Exponential Comparison Method (MPE). This method was chosen because it can determine the value of the criteria for each weight for each attribute which will then be sorted from the highest value to the lowest value to select the best prospective employees from many other prospective employees based on criteria, skills and abilities that match the company's needs with the system. This decision on the recruitment of new prospective employees will be potential and appropriate to their field of work.